Self-repairing electromagnetic wave absorbing composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202611056891.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]本发明的目的就是为了解决现有技术中存在的自修复率与强宽频吸波能力难以同时满足的问题而提供一种自修复电磁波吸收复合材料及其制备方法与应用,本发明旨在解决现有技术中自修复吸波材料吸收带宽有限、修复后性能保持率不高的问题
1.本发明将“一维磁性纳米链”(一维金属镍纳米链NC材料)与“二维碳材料”(氧化石墨烯粉末)进行复合,作为多功能填料引入自修复聚氨酯基体。该结构不仅结合了磁损耗与介电损耗的协同效应,而且二维碳材料桥接相邻的磁性纳米链,形成了更完善的三维导电与极化网络,极大地优化了材料的阻抗匹配特性与多重损耗能力。
Smart Images

Figure CN122917519A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional composite materials technology, and in particular to a self-healing electromagnetic wave absorbing composite material, its preparation method, and its application. Background Technology
[0002] With the rapid development of electronic information technology, the utilization and radiation of electromagnetic waves have experienced explosive growth. This has led to increasingly serious problems such as electromagnetic interference, information leakage, and potential health risks. Developing efficient, lightweight, and durable electromagnetic wave absorbing materials has become a research hotspot. An ideal absorbing material must meet the comprehensive requirements of being "thin, light, wide-bandwidth, and strong," meaning achieving strong absorption and wide-bandwidth coverage with the thinnest possible thickness and lightest possible weight, while also considering environmental adaptability, mechanical properties, and long-term service reliability.
[0003] Currently, common microwave absorbing materials mainly include magnetic materials (such as ferrites and metal powders), carbon-based materials (such as carbon nanotubes and graphene), and conductive polymers. Single materials often struggle to balance impedance matching and attenuation characteristics: magnetic materials have high density, low high-frequency magnetic loss, and are easily oxidized; while carbon-based materials are lightweight, their high dielectric constant leads to impedance mismatch, causing electromagnetic waves to easily reflect off their surfaces. Therefore, to overcome the limitations of single materials, combining materials with different loss mechanisms to construct heterogeneous structures has become an effective strategy for improving electromagnetic wave performance. For example, combining magnetic materials with carbon materials can achieve effective synergy between magnetic and dielectric losses.
[0004] In recent years, in addition to the pursuit of microwave absorption performance, the durability and intelligence of materials in complex environments have also attracted attention. In practical applications, microwave absorbing materials in the form of coatings or films are prone to microcracks or even macroscopic damage due to external forces, fatigue, or thermal stress, leading to the destruction of their internal loss network, a sharp decline in microwave absorption performance, and difficulty in detection and maintenance. Imparting self-healing capabilities to microwave absorbing materials, enabling them to recover their performance autonomously or through external stimulation after damage, is a revolutionary approach to extending service life and improving reliability. Intrinsic self-healing polymers, especially self-healing polyurethanes based on dynamic reversible bonds (such as Diels-Alder bonds, disulfide bonds, and multiple hydrogen bonds), are considered ideal matrices for constructing intelligent microwave absorbing materials due to their excellent mechanical toughness, designable repair efficiency, and good compatibility with functional fillers.
[0005] Chinese patent CN109053987A discloses a method for preparing a graphene / nickel composite modified waterborne polyurethane material. This application introduces the graphene / nickel composite into polyurethane via in-situ polymerization. On the one hand, the graphene / nickel composite can give the polyurethane composite material better electromagnetic radiation protection than graphene alone; on the other hand, the graphene / nickel composite can improve the mechanical properties of the polyurethane. However, while the addition of the graphene / nickel composite improves the mechanical and functional properties, it also restricts the movement of molecular chains, resulting in poor self-healing performance after damage.
[0006] Chinese patent CN120206943A discloses a self-healing broadband absorbing composite material, its preparation method, and its applications. The self-healing broadband absorbing composite material comprises a layered high-impedance matching layer and a low-impedance matching layer. The high-impedance matching layer consists of polysiloxane-modified polyurethane and composite absorbing powder, which is prepared by plasma ball milling of iron-based soft magnetic powder and insulating inorganic compounds. The low-impedance matching layer also consists of polysiloxane-modified polyurethane and soft magnetic powder. This self-healing broadband absorbing composite material possesses advantages such as excellent absorption performance, a large effective absorption bandwidth, thin thickness, good mechanical properties, and good self-healing properties. It can be used in 5G communications, new energy vehicles, consumer electronics, and national defense industries. Furthermore, its preparation method is simple and its production cost is low, making it suitable for large-scale industrial production and application. However, its high proportion of composite absorbing powder (50%~80%) does not meet the lightweight requirement of "thin, light, wide, and strong" in absorbing materials.
[0007] In summary, there is an urgent need for a self-healing electromagnetic wave absorbing composite material that can simultaneously achieve high mechanical repair rate and high functional repair rate to solve the current dilemma. Summary of the Invention
[0008] The purpose of this invention is to address the problem of simultaneously achieving high self-healing rate and strong broadband absorption capability in existing technologies by providing a self-healing electromagnetic wave absorbing composite material, its preparation method, and its applications. This invention aims to solve the problems of limited absorption bandwidth and low performance retention after repair in existing self-healing absorbing materials. By introducing the dielectric loss and conductive network of two-dimensional carbon materials, synergistic effects are achieved with the magnetic loss of magnetic nanochains, thereby obtaining a composite material with superior initial absorption performance (especially broadband absorption). Utilizing the large specific surface area and layered structure of two-dimensional materials, the magnetic nanochains are anchored to prevent excessive aggregation, while a more stable and interconnected three-dimensional conductive and polarization network is constructed within the matrix. After material damage, this network is expected to reconnect more effectively through the flow healing process of the matrix, thus simultaneously achieving high mechanical repair rate and high functional repair rate, ultimately resulting in a new generation of self-healing electromagnetic wave absorbing composite materials with superior overall performance.
[0009] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a self-healing electromagnetic wave absorbing composite material, comprising the following steps: Step S1: Dissolve the nickel source in the reaction solvent, then add the template agent and reducing agent, stir the reaction, and obtain the NC material; Step S2: Mix GO powder with water to obtain GO dispersion; Step S3: Mix the NC material obtained in step S1 with the GO dispersion obtained in step S2, and freeze-dry to obtain N3G material; Step S4: React the soft segment component, hydrophilic chain extender, and hard segment component under an inert atmosphere to obtain an SWPU solution. Step S5: Add the NG composite material obtained in step S3 to the SWPU solution obtained in step S4 and stir. Then, place the solution in a mold and dry it to obtain the target product NG. n S.
[0010] Furthermore, in step S1, the nickel source is nickel chloride hexahydrate.
[0011] Furthermore, the template agent is CTAB; the reducing agent is N2H4·H2O.
[0012] Furthermore, the mass-volume ratio of nickel source, template agent, and reducing agent in step S1 is 1-2g: 0.01-0.1g: 3-10ml.
[0013] Furthermore, the reaction temperature in step S1 is 60-80℃, and the reaction time is 0.5-2h.
[0014] Furthermore, in step S2, the mass-to-volume ratio of GO powder to water is 1g:300-700ml.
[0015] Furthermore, in step S3, the mass ratio of NC material to GO powder is 2-4:1.
[0016] Further, in step S4, the soft segment component is polytetrahydrofuran glycol; the hydrophilic chain extender is 2,2-dimethylolpropionic acid; the hard segment component is dicyclohexylmethane diisocyanate; wherein the mass ratio of the soft segment component, the hydrophilic chain extender and the hard segment component is 10-15:1:3-7, the inert atmosphere is provided by either nitrogen or helium; the reaction temperature is 70-100℃, and the reaction time is 2-4h.
[0017] In a second aspect, the present invention provides a self-healing electromagnetic wave absorbing composite material, which is obtained by any of the preparation methods described above.
[0018] In a third aspect, the present invention provides an application of a self-healing electromagnetic wave absorbing composite material in electronic devices.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention combines one-dimensional magnetic nanochains (one-dimensional nickel nanochain NC material) with two-dimensional carbon materials (graphene oxide powder) as a multifunctional filler introduced into a self-healing polyurethane matrix. This structure not only combines the synergistic effect of magnetic loss and dielectric loss, but also allows the two-dimensional carbon material to bridge adjacent magnetic nanochains, forming a more complete three-dimensional conductive and polarization network, which greatly optimizes the impedance matching characteristics and multiple loss capability of the material.
[0020] 2. This invention employs a stepwise composite process, first constructing a "magnetic-carbon" heterostructure filler, and then composites it with a polymer matrix. This method facilitates the uniform dispersion and stable existence of the functional filler in the matrix, avoids filler agglomeration, and ensures the uniformity and reliability of the composite material's properties.
[0021] 3. This invention achieves optimal broadband absorption performance at a specific thickness by precisely controlling the dielectric constant and magnetic permeability of the composite material. Experiments show that when the total mass fraction of filler is 10%, the composite material achieves an optimal effective absorption bandwidth of 8.76 GHz in the 2-18 GHz frequency range. Thanks to the robust "magnetic-carbon" network structure, even if the material is damaged, the network can be well rebuilt during the matrix self-healing process. Under the optimal formulation, after self-healing treatment (e.g., heating at 60°C for 3 hours), the effective absorption bandwidth can still recover to approximately 7.48 GHz, with a performance retention rate as high as 85.3%. Simultaneously, the tensile strength or elongation at break of the composite material of this invention can reach 78% of its original performance after self-healing, indicating its excellent comprehensive performance recovery capability. Furthermore, this material simultaneously possesses lightweight, flexibility, repairability, and strong broadband absorption characteristics, significantly improving the durability and economy of absorbing materials in complex service environments and broadening its application scenarios.
[0022] 4. The preparation method of this invention is simple, the raw materials are readily available, it is easy to scale up production, and it has good market transformation prospects. Attached Figure Description
[0023] Figure 1 SEM, EDS, and TEM images of the commercial NP and the intermediate material prepared in Example 1; wherein Figure 1 (a) is a SEM image of a commercial NP; Figure 1 (b) is a SEM image of the NC material; Figure 1 (c) is a SEM image of N3G material; Figure 1 (d1) Figure 1 (d2) Figure 1(d3) is the EDS image of the NC material; Figure 1 (e1) Figure 1 (e2) Figure 1 (e3) is an EDS image of N3G material; Figure 1 (f) is a TEM image of a commercial NP; Figure 1 (g) is a TEM image of the NC material; Figure 1 (h) is a TEM image of N3G material; Figure 2 Infrared, XRD, and hysteresis loop images of commercial NP, the GO dispersion prepared in Example 1 of this invention, and the N3G material; wherein: Figure 2 (a) Infrared spectra of GO dispersion and N3G material; Figure 2 (b) XRD patterns of commercial NP, NC and N3G materials; Figure 2 (c) Hysteresis loop diagrams of commercial NP, NC and N3G materials; Figure 3 The infrared spectrum, strain map, and image of the healed specimen of the SWPU solution prepared in Example 1 of this invention are shown below: Figure 3 (a) is the FTIR infrared spectrum; Figure 3 (b) is a tensile stress-strain diagram before and after healing; Figure 3 (c) is a photograph of the actual healing process; Figure 4 The NP prepared by mixing commercial NP with SWPU solution in different mass ratios in Comparative Example 2 of this invention n A two-dimensional RL diagram of S; where Figure 4 (a) The mass ratio of commercial NPs is 5%; of which Figure 4 (b) The mass ratio of commercial NPs is 10%; among which Figure 4 (c) The mass ratio of commercial NPs is 15%; among which Figure 4 (d) The mass ratio of commercial NPs is 20%; Figure 5 The NC materials prepared by mixing NC materials with SWPU solution in different mass ratios as described in Comparative Example 1 of this invention are NC materials prepared by mixing NC materials with SWPU solution in different mass ratios. n A two-dimensional RL diagram of S; where Figure 5 (a) The mass ratio of NC material is 5%; among which Figure 5 (b) The mass ratio of NC material is 10%; among which Figure 5 (c) The mass ratio of NC material is 15%; among which Figure 5 (d) The mass ratio of NC material is 20%; Figure 6 The NG material prepared by mixing N3G material with SWPU solution in different mass ratios as described in Example 1 of this invention is an example of an invention. n A two-dimensional RL diagram of S; where Figure 6 (a) The mass ratio of N3G material is 5%; of which Figure 6 (b) The mass ratio of N3G material is 10%; of which Figure 6 (c) The mass ratio of N3G material is 15%; among which Figure 6 (d) The mass ratio of N3G material is 20%; Figure 7 The products NG prepared in Example 1 are respectively 10 Actual photos of S-cut and self-healing objects after bending, twisting, and bearing load; Figure 8 The products NG prepared in Example 1 are respectively 10 Optical microscope images of S self-healing at 0h, 3h, 6h, and 18h; Figure 9 NG, the product prepared in Example 1 10 S-self-healing tensile properties and two-dimensional RL diagram; where Figure 9 (a) is NG n Comparison of tensile properties of S original and self-healing after 18 hours; Figure 9 (b) is the original product NG n A two-dimensional RL diagram of S; Figure 9 (c) is NG n Two-dimensional RL image of S 3 hours after self-healing. Detailed Implementation
[0024] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0025] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, each point or individual value between the endpoints of a range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value, or combined with other lower or upper limits, to form a range not explicitly stated. In the description of this application, it should be noted that, unless otherwise stated, "above" includes the stated number, and "multiple" in "one or more" means two or more.
[0026] The foregoing description of this application is not intended to describe every disclosed implementation or method. Instead, the following description provides more specific examples of exemplary embodiments. Throughout the application, guidance is provided through a series of embodiments that can be used in various combinations. The examples listed are representative only and should not be construed as exhaustive.
[0027] Numerous details are explored in the following description to provide a more thorough explanation of embodiments of this application; however, it will be apparent to those skilled in the art that embodiments of this application may be practiced without these specific details.
[0028] To further understand the present invention, the following embodiments are provided. It is worth noting that, unless otherwise specified, all raw materials used in the present invention are commercially available; and all methods and equipment employed are common in the art.
[0029] Example 1: A type of NG n The S composite material is prepared through the following steps: (1) Add 1.19g NiCl2·6H2O and 1.2g NaOH to 100mL of ethylene glycol and stir until completely dissolved to obtain solution A; (2) Add 0.04g CTAB and 6mL N2H4·H2O to solution A obtained in step (1) and stir for 1h. Then, heat to 70℃ and keep warm for 1h without stirring. Wash the product with deionized water and then dry it in an oven at 60℃ for 12h to obtain NC material. (3) Add 0.1g of graphene oxide (GO) powder to 50ml of deionized water and sonicate for 1h to obtain a uniform GO dispersion. (4) Add 0.3g of the NC material obtained in step (2) to the GO dispersion obtained in step (3) under continuous stirring, stir continuously for 2h, add 4mL of N2H4·H2O, react at 90℃ for 1h, wash and freeze dry for 24h to obtain the product N3G material. (5) 10g of polytetrahydrofuran diol (PTMEG-2000), 0.8g of 2,2-dimethylolpropionic acid (DMPA) and 4g of dicyclohexylmethane diisocyanate (HMDI) were stirred at 85°C for 3 h under N2 atmosphere, then cooled to 40°C, 0.7g of diaminodiphenyl disulfide (2S) was added and reacted for 3 h, and then 0.6g of TEA and 40ml of deionized water were added to obtain a homogeneous SWPU solution; (6) Add the N3G material obtained in step (4) to the SWPU solution obtained in step (5) at a mass ratio of 5-20% and stir for 2 hours. Then, place the mixed solution in a polytetrafluoroethylene mold to dry, and obtain the product NG. n S. The preferred mass ratios of N3G material are 5%, 10%, 15%, and 20%, and the products prepared using these corresponding N3G material mass ratios are named NG5S, NG, and NG, respectively. 10 S, NG 15 S, NG 20 S.
[0030] Comparative Example 1: A type of NC n The S composite material is prepared through the following steps: (1) 1.19g NiCl2·6H2O and 1.2g NaOH were added to 100mL of ethylene glycol and stirred until completely dissolved to obtain solution A; (2) Add 0.04g CTAB and 6mL N2H4·H2O to solution A obtained in step (1) and stir for 1h. Then, heat to 70℃ and keep warm for 1h without stirring. Wash the product with deionized water and then dry it in an oven at 60℃ for 12h to obtain NC material. (3) 10g PTMEG-2000, 0.8g DMPA and 4g HMDI were stirred at 85℃ for 3 h in the presence of N2, then cooled to 40℃, 0.7g 2S was added and reacted for 3 h, and then 0.6g TEA and 40ml deionized water were added to obtain a homogeneous SWPU solution. (4) Add the NC material obtained in step (2) to the SWPU solution obtained in step (3) at a mass ratio of 5-20% and stir for 2 hours. Then, place the mixed solution in a polytetrafluoroethylene mold to dry and obtain the product NC. n S. The preferred mass ratios of NC materials are 5%, 10%, 15%, and 20%, and the products prepared using these corresponding NC material mass ratios are named NC5S, NC5S, and NC5S, respectively. 10 S, NC 15 S, NC 20 S.
[0031] Comparative Example 2: A type of NC n The S composite material is prepared through the following steps: (1) PTMEG-2000, DMPA and HMDI were stirred at 85°C for 3 h in the presence of N2, then cooled to 40°C, 0.7 g of 2S was added and reacted for 3 h, and then 0.6 g of TEA and 40 ml of deionized water were added to obtain a homogeneous SWPU solution. (2) Add commercial NP to the SWPU solution obtained in step (1) at a mass ratio of 5-20% and stir for 2 hours. Then, place the mixed solution in a polytetrafluoroethylene mold to dry and obtain the product NP. n S. The preferred mass ratios are 5%, 10%, 15%, and 20%, and the products prepared using the corresponding commercially available NP mass ratios will be named NP5S, NP, etc., respectively. 10 S, NP 15 S, NP 20 S.
[0032] The product NG obtained in Example 1 and Comparative Examples 1-2 was characterized using the following methods. n S, NC n S and NC n S performs test analysis: (1) Morphological characterization: The micro morphology of the sample (such as particle size, distribution and surface features) is observed by SEM, the internal structure and lattice fringes of the sample are observed by TEM, and the macro morphology of the sample (such as color, transparency and flexibility) is recorded by taking physical photos.
[0033] (2) Physical analysis: XRD is used to analyze the crystal structure and phase composition of the sample, EDS is used to determine the element types and distribution of the sample, VSM is used to determine the hysteresis loop and magnetic properties of the sample, and infrared spectroscopy is used to identify the organic functional groups and chemical bonding states in the sample.
[0034] (3) Electromagnetic wave absorption performance measurement: The electromagnetic properties of the sample in the microwave band, such as S-parameters, complex permittivity / complex permeability and reflection loss (RL), are measured by VNA; the tensile / compressive strength, elastic modulus and elongation at break of the sample are measured by mechanical testing system.
[0035] Results analysis: Morphology analysis: This study investigated the microstructure and morphology of the three commercially available microwave absorbing agents (NP, NC, and N3G materials) used in Example 1 and Comparative Examples 1-2. Figure 1 (a) is a SEM image of a commercial NP; Figure 1 (b) is a SEM image of the NC material; Figure 1 (c) is a SEM image of N3G material; Figure 1 (d1) Figure 1 (d2) Figure 1 (d3) is the EDS image of the NC material; Figure 1 (e1) Figure 1 (e2) Figure 1 (e3) is an EDS image of N3G material; Figure 1 (f) is a TEM image of a commercial NP; Figure 1(g) is a TEM image of the NC material; Figure 1 (h) is a TEM image of N3G material. Figure 1 (a) is a microscopic image of nickel particles. Figure 1 (b) is a scanning electron microscope image of a nickel chain composed of individual nickel particles, combined with... Figure 1 (a) and Figure 1 (b) shows the successful synthesis of the nickel chain component. From Figure 1 (c) The scanning electron microscope image of the NG material clearly shows that the nickel chains are completely covered by rGO sheets, and the numerous edge planes of rGO are vertically arranged on the surface of the nickel chains, exhibiting a hierarchical core-shell structure. Figure 1 (d1)- Figure 1 As can be seen in (d3), the Ni element distribution highly overlaps with the corresponding SEM image, indicating the successful preparation of the nickel chain. Figure 1 (e1)- Figure 1 As can be seen in (e3), the Ni element distribution highly overlaps with the nickel chain portion in the corresponding SEM image, indicating that the rGO sheet successfully covers the Ni chain. From Figure 1 (f) is a TEM micrograph of nickel particles. Figure 1 The TEM image of (g) also shows an image of nickel chains composed of individual nickel particles. From Figure 1 The TEM image in (h) shows that the N3G material prepared by this invention has a hierarchical core-shell structure, further verifying that this invention has successfully prepared an N3G material with a core-shell structure. Figure 1 Image verification results show that the nickel chain used in Example 1 of this invention is completely covered by transparent rGO sheets, giving the rGO / Ni nanofibers abundant edge planes and a large specific surface area. Furthermore, EDS elemental mapping also indicates that the rGO sheets successfully cover the Ni chain.
[0036] Phase analysis: Figure 2 Infrared, XRD, and hysteresis loop images of commercial NP, the GO dispersion prepared in Example 1 of this invention, and the N3G material. Wherein: Figure 2 (a) Infrared spectra of GO dispersion and N3G material; Figure 2 (b) XRD patterns of commercial NP, NC and N3G materials; Figure 2 (c) shows the hysteresis loop diagrams of commercial NP, NC, and N3G materials. From Figure 2 As can be seen in (a), after chemical reduction, the peak intensity of the hydroxyl group in NG decreased significantly, while the peaks of oxygen-containing functional groups disappeared. Therefore, it can be concluded that GO has been reduced to rGO. Figure 2As can be seen in (b), characteristic diffraction peaks of the (111), (200) and (220) crystal planes (JCPDS No. 04-0850) corresponding to nickel can be seen in commercial NP, NC and N3G materials, confirming that the phase composition of NP, NC and NG contains nickel. Figure 2 (c) Shows the hysteresis loops of commercially available NP, NC, and N3G materials. Due to the one-dimensional anisotropy of the nickel chain, NC exhibits the highest saturation magnetization. The presence of nonmagnetic rGO nanosheets results in a lower saturation magnetization for NG compared to pure nickel chains, but it is still higher than that of nickel particles. This indicates that all samples maintain ferromagnetic behavior, and the saturation magnetization and coercivity are modulated by the graphene content.
[0037] Substrate analysis: To verify the successful synthesis of SWPU in Example 1 of this invention, FTIR infrared spectroscopy analysis was performed, and the obtained infrared spectrum is shown below. Figure 3 As shown in (a), from Figure 3 (a) shows that -S = S - (~500cm) in the precursor. -1 The self-healing agent was successfully introduced into the matrix, endowing it with self-healing properties. Tensile tests were performed to quantitatively characterize its self-healing properties, and the resulting strain diagram is shown below. Figure 3 As shown in (b), from Figure 3 As shown in (b), after SWPU is decomposed into two segments and exposed to 60°C for 18 hours, its ultimate tensile strength recovers to 20 MPa, and the η value (healing efficiency) can reach 94%. Figure 3 (c) is a photograph of the actual healing process, from... Figure 3 As shown in (c), the substrate was completely repaired after 18 hours, and the repaired substrate had no gaps or other defects, indicating that the substrate has good self-healing properties.
[0038] Electromagnetic wave absorption performance analysis: To analyze the electromagnetic wave absorption performance of the filler and matrix composite, three microwave absorbing agents were composited with SWPU in different proportions, and their electromagnetic wave absorption performance was tested and analyzed. The results are as follows: Figure 4-6 As shown, where Figure 4-6 NP n S, NC n S and NG n The two-dimensional RL diagram of material S, where: Figure 4 (a) The mass ratio of commercial NPs is 5%; of which Figure 4 (b) The mass ratio of commercial NPs is 10%; among which Figure 4 (c) The mass ratio of commercial NPs is 15%; among which Figure 4 (d) The mass ratio of commercial NPs is 20%; Figure 5 (a) The mass ratio of NC material is 5%; among which Figure 5(b) The mass ratio of NC material is 10%; among which Figure 5 (c) The mass ratio of NC material is 15%; among which Figure 5 (d) The mass ratio of NC material is 20%; Figure 6 (a) The mass ratio of N3G material is 5%; of which Figure 6 (b) The mass ratio of N3G material is 10%; of which Figure 6 (c) The mass ratio of N3G material is 15%; among which Figure 6 In (d), the mass ratio of N3G material is 20%. From Figure 4 As can be seen from this, NP n S at commercial NP mass ratios of 5% and 10%, R L The values are generally greater than -10dB, indicating no effective wave absorption capability. Limited electromagnetic wave absorption performance only appears when the filling amount is 15wt%. This suggests that one-dimensional nickel chains have superior performance compared to zero-dimensional nickel particles. (Compared to NP...) n Unlike other materials, NC5S exhibits effective microwave absorption capabilities (RL < -10 dB) even at a low filler content of 5 wt%. As the filler content increases, the effective absorption bandwidth expands, covering a wider frequency-thickness range. Furthermore, compared to zero-dimensional nickel particles, the chain-like one-dimensional nickel chains demonstrate superior absorption performance at all three filler contents, indicating its suitability as a high-performance microwave absorbing material. However, increasing the proportion has limited improvement on absorption performance. Therefore, we employed a magneto-electric composite approach, combining NC5S with graphene and then incorporating it into a SWPU matrix, analyzing its microwave absorption characteristics. The results are as follows... Figure 6 As shown. From Figure 6 It can be observed that its electromagnetic wave absorption capability is greatly improved, and NG 10 The S sample was particularly notable, achieving an RL of -52.64 dB at a thickness of 2.8 mm. min The product achieved an EAB of 8.76 GHz (7.2 ~ 15.96 GHz) at 2.6 mm, effectively covering the X-band, demonstrating that the NG product prepared in this invention... 10 S has a strong wave absorption capability.
[0039] Figure 7 The products NG prepared in Example 1 are respectively 10 Actual photos of S-cut and self-healing specimens after bending, torsion, and load-bearing, from... Figure 7 As can be seen from the above, the product NG prepared in Example 1 of this invention... 10 S has a good self-healing effect. NG 10 S can re-heal after being completely severed, and after healing, it maintains good flexibility, can withstand complex deformations such as bending and torsion, and can suspend a 100 g weight without breaking.
[0040] Repair performance analysis: To monitor the self-healing behavior of the composite material, we used the NG prepared in Example 1 as a reference. 10 Sample S was cut in half, and the two ends were gently brought together. The healed material could still be bent, twisted, and bear weight without breaking. The optical microscopic results are as follows: Figure 8 As shown, where, Figure 8 (a) Figure 8 (b) Figure 8 (c) Figure 8 (d) Optical microscope images of the self-healing process at 0h, 3h, 6h, and 18h, respectively. From Figure 8 As can be seen, the cracks on the material surface become significantly shallower with increasing healing time, until they almost completely disappear, indicating that the product NG prepared in this invention... 10 S has strong self-healing properties.
[0041] Figure 9 NG, the product prepared in Example 1 10 S-self-healing tensile properties and two-dimensional RL diagram; where Figure 9 (a) is NG n Comparison of tensile properties of S original and self-healing after 18 hours; Figure 9 (b) is the original product NG 10 A two-dimensional RL diagram of S; Figure 9 (c) is NG 10 Two-dimensional RL image of S 3 hours after self-healing. From Figure 9 As shown in (a), the material's mechanical self-healing rate (defined as recovered tensile strength / original tensile strength) is 78% within 18 hours. After sufficient healing, the material can recover most of its toughness. Three hours after self-healing, its two-dimensional RL plot is shown below. Figure 9 As shown in (c), it is similar to the original two-dimensional RL graph (i.e. Figure 9 (b) Compared to this, the effective absorption bandwidth can still be restored to approximately 7.48 GHz, with a performance retention rate as high as 85.3%. In addition, in terms of repair time, the recovery speed of electromagnetic wave absorption performance is much faster than that of mechanical healing.
[0042] The foregoing has shown and described the basic process, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a self-healing electromagnetic wave absorbing composite material, characterized in that, Includes the following steps: Step S1: Dissolve the nickel source in the reaction solvent, then add the template agent and reducing agent, stir the reaction, and obtain the NC material; Step S2: Mix GO powder with water to obtain GO dispersion; Step S3: Mix the NC material obtained in step S1 with the GO dispersion obtained in step S2, and freeze-dry to obtain N3G material; Step S4: React the soft segment component, hydrophilic chain extender, and hard segment component under an inert atmosphere to obtain an SWPU solution. Step S5: Add the NG composite material obtained in step S3 to the SWPU solution obtained in step S4 and stir. Then, place the solution in a mold and dry it to obtain the target product NG. n S.
2. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, In step S1, the nickel source is nickel chloride hexahydrate.
3. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, The template agent is CTAB; the reducing agent is N2H4·H2O.
4. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, The mass-volume ratio of nickel source, template agent and reducing agent in step S1 is 1-2g: 0.01-0.1g: 3-10ml.
5. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, The reaction temperature in step S1 is 60-80℃, and the reaction time is 0.5-2h.
6. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, In step S2, the mass-to-volume ratio of GO powder to water is 1g:300-700ml.
7. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, In step S3, the mass ratio of NC material to GO powder is 2-4:
1.
8. The method for preparing a self-healing electromagnetic wave absorbing composite material according to claim 1, characterized in that, In step S4, the soft segment component is polytetrahydrofuran glycol; the hydrophilic chain extender is 2,2-dimethylolpropionic acid; and the hard segment component is dicyclohexylmethane diisocyanate. The mass ratio of the soft segment component, the hydrophilic chain extender, and the hard segment component is 10-15:1:3-7. The inert atmosphere is provided by either nitrogen or helium. The reaction temperature is 70-100℃, and the reaction time is 2-4 hours.
9. A self-healing electromagnetic wave absorbing composite material, obtained by any one of the preparation methods described in claims 1-8.
10. The application of a self-healing electromagnetic wave absorbing composite material as described in claim 9 in electronic devices.
Citation Information
Patent Citations
Graphene / nickel compound modified waterborne polyurethane material preparation method
CN109053987A
Self-repairing broadband wave-absorbing composite material as well as preparation method and application thereof
CN120206943A